Externalities of Mandatory IFRS Adoption: Evidence from Cross-Border Spillover Effects of Financial Information on Investment Efficiency - Chen, Chen; Young, Danqing; Zhuang, Zili (The Accounting Review, 2013)
ABSTRACT This study examines the externalities of mandatory IFRS adoption on firms' investment efficiency in 17 European countries. We use the ROA difference between the firm and its peers to proxy for the information on the peers' investment performance. We find that the spillover effect of a firm's ROA difference versus its foreign peers, but not domestic peers, on the firm's investment efficiency increases after IFRS adoption. We also find that increased disclosure by both foreign and domestic peers after IFRS adoption has a spillover effect on a firm's investment efficiency. Further, a firm's investment changes induced by its ROA difference versus foreign peers are more value-relevant after IFRS adoption, and those induced by increased disclosure by foreign peers under IFRS are value-relevant. Additional analyses reveal that our results are affected by legal enforcement strength, peer composition, and industry competition. Overall, we document positive externalities of mandatory IFRS adoption. Data Availability: Data are available from commercial providers (Worldscope, DataStream, and I/B/E/S).